ANALISIS FAKTOR RISIKO PEMBERIAN ASI DAN VENTILASI KAMAR TERHADAP KEJADIAN PNEUMONIA BALITA - Bagus Ali Fikri (The Indonesian Journal of Public Health, 2016)
Pneumonia is still a major cause of infant mortality in the world amounted to 18% of infant  mortality caused by pneumonia, nor in Indonesia amounted to 13% of infant mortality contributed by  pneumonia and pneumonia incidence was highest in children aged 1–4 years. Some of the possible interventions to reduce the incidence of pneumonia is exclusive breastfeeding, immunization that associated with pneumonia, and reduce air pollution in the house. This type of research is an analytic  observational with case control design. Case population is all toddlers diagnosed with pneumonia in  the August to December 2015 period, while the control population is all children who are diagnosed  does not pneumonia in the period. The method used for this research is total sampling which resulted  of 40 toddlers. The independent variables used were a history of exclusive breastfeeding and the room  ventilation. The results of this study are exclusive breastfeeding (OR = 7.407) and the room ventilation  (OR = 13.5) at risk for pneumonia. Based on these results the government must improve the dissemination  of exclusive breastfeeding, one of them with advertising. Parents of toddlers must improve air circulation  in the room by improving size of ventilation or manipulate the air condition of toddler room to better  circulation, of one of them by giving the fan and blower installation in toddler rooms.Keywords:exclusive breastfeeding, risk factor, room ventilation, toddler pneumonia.